PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Sihombing, Mey Wina; Tipa, Handra (SCIENTIA JOURNAL, 2021)
The purpose of this study is to analyze individually and jointly the influence of taxpayer awareness, knowledge and taxation sanctions on mandatory compliance personal tax at Tax Service Office KPP Pratama Batam Selatan. Data collection is done by questionnaire calculated on a likert scale. The population taken from the taxpayers of private persons who have registered in KPP Pratama Batam Selatan which amount to 346.894 people and the sample is determined by using the calculation of slovin formula. From the calculation of slovin formula obtained the number of samples as many as 100 respondents taxpayers personal person. The data analysis method used in this study is a quantitative data, analysis method with data collection techniques, namely descriptive analysis, validity test, reliability test, multiple linear regression test, normality test, multicolonierity test, heteroskedastisity test, F test, T test, and determination test. The result of this study showed that taxpayer awareness variabels have a significant effect on the compliance of private taxpayers in KPP Pratama Batam Selatan, tax sanctions variables have a significant effect on the compliance of private taxpayers in KPP Pratama Batam Selatam, and knowledge variables have no significant effect on the compliance of private taxpayers in KPP Pratama Batam Selatan. Keywords: Taxpayers Awareness; Knowledge; Tax Sanctions; Private Person Taxpayer Compliance